Application of electronic management at the Algerian University - Nahed, Belgoumri; Nassima, Tadjine (The International tax journal, 2025)
Electronic management is considered as the most important type of modern management where the institutions in general and the universities in particular seek through them to keep all the developments which take place in our daily life, but the application of this management requires capabilities and mechanisms for its success. The main aims of this research paper are to identify the type of the electronic management and its most important applications at the Algerian University, in addition to identify the challenges it faces through applying this type of administration, these challenges represent the obstacles related to the basic requirements that must be available for the success of this administration, such as: the equipments and the necessity to provide people with the Internet, in addition to the qualified human resource, and the laws that regulate them.